Variability in clubhead presentation characteristics and ball impact location for golfers' drives - Betzler, N. F.; Monk, S. A.; Wallace, E. S.; Otto, S. R. (Journal of Sports Sciences, 2012)
The purpose of the present study was to analyse the variability in clubhead presentation to the ball and the resulting ball impact location on the club face for a range of golfers of different ability. A total of 285 male and female participants hit multiple shots using one of four proprietary drivers. Self-reported handicap was used to quantify a participant's golfing ability. A bespoke motion capture system and user-written algorithms was used to track the clubhead just before and at impact, measuring clubhead speed, clubhead orientation, and impact location. A Doppler radar was used to measure golf ball speed. Generally, golfers of higher skill (lower handicap) generated increased clubhead speed and increased efficiency (ratio of ball speed to clubhead speed). Non-parametric statistical tests showed that low-handicap golfers exhibit significantly lower variability from shot to shot in clubhead speed, efficiency, impact location, attack angle, club path, and face angle compared with high-handicap golfers.